Biological assessment of European lakes: ecological rationale and human impacts. (18th February 2013) - Brucet, Sandra; Poikane, Sandra; Lyche‐Solheim, Anne; Birk, Sebastian
Summary Nearly one hundred biological methods are currently used to assess the ecological status of European lakes. Here, using information from a questionnaire, complemented with findings from the literature, we compared the use of different methods to assess the ecological status of lakes as well as the rationale for using different organism groups (phytoplankton, benthic diatoms, macrophytes, benthic invertebrates and fish) in monitoring programmes. Reference conditions were estimated for about half of the methods using near‐natural reference sites, complemented with other approaches, such as historical data, modelling and expert judgment. About 40% of the methods used more subjective approaches to establish reference conditions (e.g. selecting near‐natural reference sites without any pressure criteria) or no information was available. Methods using several measures (i.e. multimetric methods) were developed, with particular emphasis on measures based on sensitivity/tolerance and abundance. Different organisms showed different responses to similar levels of human impacts. Assessment methods based on phytoplankton showed the strongest response to eutrophication, with class boundaries mainly based on ecological rationale. By contrast, statistical distributions and expert judgment were frequently used in setting class boundaries in macrophyte, benthic invertebrates and fish methods. Methods were strongly biased towards detecting changes associated with eutrophication, with other pressures (e.g. hydromorphological alteration) seldom monitored. Effective restoration measures and achieving good ecological status of European lakes will require assessment programmes based on a sound understanding of pressure–response relationships as well as the use of ecologically based approaches in establishing reference conditions and setting class boundaries.